2004
DOI: 10.32398/cjhp.v2i1.573
|View full text |Cite
|
Sign up to set email alerts
|

Viewpoints on Accreditation from Health Education Professionals and Administrators of Academic Professional Preparation Programs

Abstract: The health education profession has made significant strides in promoting quality assurance for credentialing of health educators through a combination of individual certification and program approval and accreditation mechanisms. Although the profession has widely embraced individual certification, program accreditation has not been uniformly accepted nor implemented. The National Task Force on Accreditation in Health Education was charged to develop a detailed plan for a coordinated accreditation system for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…As health educators in practice, most participants worked in either community or public health or a college or university (Bernhardt et al, 2003;Birch & Pearson, 1995;Hayden, 1990;Mail, 1993;Jenkins & Olsen, 1994;Prelip, 2001). Compared to health educators in other studies (Clark et al, 1998;Matthews et al, 2004), participants in this study had a higher average income, with nearly one third earning more than $45,000 annually.…”
Section: > >Discussionmentioning
confidence: 73%
“…As health educators in practice, most participants worked in either community or public health or a college or university (Bernhardt et al, 2003;Birch & Pearson, 1995;Hayden, 1990;Mail, 1993;Jenkins & Olsen, 1994;Prelip, 2001). Compared to health educators in other studies (Clark et al, 1998;Matthews et al, 2004), participants in this study had a higher average income, with nearly one third earning more than $45,000 annually.…”
Section: > >Discussionmentioning
confidence: 73%
“…(As discussed in this article, NCATE and TEAC are currently in discussion about a unified accrediting system in educator preparation.) The Accreditation Task Force decided against creating any new singular accreditation body for health education as research showed that CEPH and NCATE were already widely embraced by administrators, faculty, and practitioners 14 . Moreover, the first of the Task Force recommendations stated that accreditation should replace existing approval mechanisms in an orderly fashion; thus when the 2004 recommendations are fully implemented, SABPAC will be eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the Task Force conducted two Web-based surveys to assess viewpoints on accreditation and program approval for graduate and undergraduate programs in health education (Bernhardt et al, 2003). Not only were these surveys a good way to collect information, but they also served as a focal point for disseminating the overall value of accreditation at both the individual and programmatic level.…”
Section: Web-based Surveysmentioning
confidence: 99%